Implications of research practices in STEM on establishing research data management services the case of UP Diliman - Dumlao, Mark Xavier G.
Research data management service is a relatively new service that is gaining popularity in the west due to its importance. In UP Diliman. despite having a high number of research activities, there is no library currently with this service. This thesis aims to find out what caused the lack of ROM service. Specifically, it looked into the data management practices and needs of UP Diliman researchers. It also looks into the infrastructures of UP Diliman libraries and the services they offer in relation to ROM.